ANALYSIS OF THE ECONOMIC / FINANCIAL EFFICIENCY OF COMPANIES THAT BELONG TO BRAZILIAN AGRIBUSINESS - Diel, Fábio José; Diel, Elisandra Henn; Schulz, Sheila Jeane; Chiarello, Tânia Cristina; da Silva, Tarcísio Pedro (Contextus - Revista Contemporânea de Economia e Gestão, 2014)
The main objective of the study was to analyze the financial and economic efficiency of agricultural enterprises, agribusiness, listed in BM&FBovespa as consumer staples sector. The method used was the Data Envelopment Analysis (DEA). The research is characterized as descriptive, documentary and quantitative. As result, it is concluded that the larger number of indication of agribusiness companies that were considered benchmark for others reached the amount of 8 nominations, and in 2008 none of these companies had indicated. In 2011, the last year analyzed, 23 of the 41 listed companies in the consumer staples sector belonged to agribusiness, and 12 of them had 100% efficiency.